Key anthropometric variables associated with front-crawl swimming performance in youth swimmers: an allometric approach - Sammoud, S.; Negra, Y.; Chaabene, H.; Bouguezzi, R.; Attia, A.; Granacher, U.; Younes, H.; Nevill, A. M. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to establish key anthropometric characteristics (e.g., optimal body height, limb-segment length, and girth/breadth ratios) related to 100-m front-crawl performance in young swimmers. In total, 74 swimmers (boys [n = 41; age: 18.1 ± 3.5 years]; girls [n = 33; age: 15.9 ± 3.1 years]) participated in this study. We adopted a multiplicative allometric log-linear regression model to identify key anthropometric characteristics associated with 100-m front-crawl swimming performance. The main outcomes indicated that length ratio = ([height/leg length]), foot length and ankle girth, biacromial breadth, and % of body fat were associated with 100-m front-crawl mean swimming speed performance. These findings highlight the importance of assessing anthropometric characteristics in young front-crawl swimmers for talent identification and development.